Effects of injectable trace minerals administered concurrently with a modified live virus vaccine on long-term protection against bovine viral diarrhea virus acute infection in dairy calves. (August 2018) - Bittar, J.H.J.; Hoyos-Jaramillo, A.; Hurley, D.J.; Woolums, A.R.; Havenga, L.J.; Lourenço, J.M.; Barnett, G.; Gomes, V.; Saliki, J.T.; Harmon, D.D.; Palomares, R.A.
Abstract: The objective was to evaluate the effects of injectable trace minerals (ITM) concurrent with modified-live virus (MLV) vaccination on protection from bovine viral diarrhea virus (BVDV) infection in dairy calves. In a previous study (Palomares et al., 2016), thirty dairy calves received two doses of a MLV vaccine subcutaneously (SC), concurrently with ITM ( n = 15) or saline (n = 15), SC. Five months later, 20 of these calves received ITM (G1, n = 10) or saline (G2, n = 10) according to their previous groups and were challenged intranasally with BVDV2. Five unvaccinated calves were also challenged with BVDV2 (G3). Blood samples were collected on days 0 (BVDV challenge), 3, 5, 6, 7, 8, 9, 11, 14, 18, 21, 32 and 61 for leukocyte count, virus isolation and BVDV serum neutralizing antibodies (SNA). Mild-moderate clinical signs were observed in G3 after BVDV challenge. Group 1 showed lower sum health score and nasal score on d5 and fecal score on d8 compared to G2. Rectal temperature and leukocyte counts were not different between G1 and G2. In contrast, G3 calves had significant leukopenia and lymphopenia from d3 to d7 ( P < .05) and higher rectal temperatures on d6 to d8, compared to values on d0 ( P < .05). All unvaccinated calves became viremic, while viremia was not detected in G1 or G2. Average daily gain was not different between vaccinated groups, however, only G1 calves had significantly greater ( P = .04) ADG compared to non-vaccinated calves during the first 14 days post challenge. Vaccinated calves treated or not with ITM were protected from BVDV2 infection five months post-vaccination. Highlights: Vaccinated calves treated or not with ITM were protected from BVDV2 infection five months post-vaccination. Moderate disease was observed in G3 calves after challenge. G1 calves had lower health, nasal and fecal scores than G2. G3 calves had significant leukopenia/lymphopenia on d3-d7 and higher rectal temperature on d6-d8, compared to values on d0. ADG was not different between vaccinated groups. Only ITM-treated calves had greater ADG than non-vaccinated calves.